Is a 10 trillion euro European climate investment initiative fiscally sustainable? - Jakob Kapeller; Stuart Leitch; Rafael Wildauer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
This policy study asks to what extent large-scale public investment efforts could be a viable tool to provide the necessary infrastructure to break Europe's dependency on fossil fuel and carbon emissions more broadly. We estimate semi-structural VAR models for the EU27. These are used to study the impact of permanent as well as 5-year long public investment programmes. Three key findings emerge: First, government investment multipliers for the EU27 are large and range from 5.12 to 5.25. Second, debt-to-GDP ratios are likely to fall in response to the strong economic impulse generated by additional public investment spending. The study therefore classifies additional public investment spending in the EU27 as sustainable fiscal policy. Third, single country investment initiatives will likely lead to smaller economic expansions when compared to coordinated EU-wide investment, due to Europe's strong intra-member state trade flows. A coordinated approach to fiscal policy is thus substantially more effective not only when it comes to delivering network-dependent infrastructure (rail, grid) but also with respect to the economic stimulus it creates.
Keywords: E62; H63; 330